Peracangan Kemasan makanan Ringan Kacang Sihobuk Produksi â€œUD. TADODOâ€ sebagai Media promosi - Sinaga, Rommel; Simangunsong, Sahban (XXX-XXX)
In recent years the development of the business world has progressed quite rapidly, in order to survive the company must have an effective marketing solution, one of which is by doing a packaging design.Â Indirect packaging is very influential in a product marketing because packaging is not only a company's professionalism, even packaging is also used as a branding / corporate identity to increase buyer interest.How to design packaging for processed yakobuk beans. TADODO in order to become a corporate identity and be able to become a solution in marketing. With the packaging design, people will get to know UD. TADODO as a business that produces sihobuk beans thus increasing buyer interest.